2004
DOI: 10.1021/ie030686e
|View full text |Cite
|
Sign up to set email alerts
|

On the Tuning of Predictive Controllers:  Inverse Optimality and the Minimum Variance Covariance Constrained Control Problem

Abstract: This paper presents a systematic tuning approach for linear model predictive controllers based on the computationally attractive minimum variance covariance constrained control (MVC 3 ) problem. Unfortunately, the linear feedback policy generated by the MVC 3 problem is incompatible with the algorithmic framework of predictive control, in which the primary tuning vehicle is the selection of objective function weights. The main result of this paper is to show that all linear feedbacks generated by the MVC 3 pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 25 publications
0
43
0
Order By: Relevance
“…The constrained minimum variance (CMV) control problem, defined in Chmielewski & Manthanwar (2004) is:…”
Section: Lqg and Inventory Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…The constrained minimum variance (CMV) control problem, defined in Chmielewski & Manthanwar (2004) is:…”
Section: Lqg and Inventory Controlmentioning
confidence: 99%
“…In Chmielewski and Manthanwar (2004), it is shown that all controllers generated by the CMV problem are equal to some LQG controller.…”
Section: Lqg and Inventory Controlmentioning
confidence: 99%
“…In the first installment (Chmielewski and Manthanwar, 2004) of this series on the tuning of predictive controllers, (Chmielewski and Manthanwar, 2004;Omell and Chmielewski, 2014) it was shown that the linear feedback generated by the minimum variance covariance constrained control (MVC 3 ) problem is guaranteed to be in the family of Linear Quadratic Regulator (LQR) feedback policies. In addition, using the inverse optimality results of Chmielewski and Manthanwar (2004), one could generate quadratic objective function weights such that if used within the LQR problem, the resulting controller would be identical to the MVC 3 policy.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, using the inverse optimality results of Chmielewski and Manthanwar (2004), one could generate quadratic objective function weights such that if used within the LQR problem, the resulting controller would be identical to the MVC 3 policy. It was then postulated that such a scheme could be used within a predictive controller context to tune the controller (i.e., select quadratic objective function weights) such that the weights and the point-wise-in-time constraints would be in alignment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation